INTERACTION BETWEEN ORGANOPHOSPHATE INSECTICIDE AND PROTOX-INHIBITING HERBICIDES AND ITS IMPLICATION IN THE RESISTANCE OF Euphorbia heterophylla - TREZZI, Michelangelo Muzell; NUNES, Anderson Luis; PORTES, Emerson da Silva (Scientia Agraria, 2009)
Herbicide metabolization is one of the mechanisms that confers herbicide resistance to weeds. Organophosphate insecticides inhibits enzymes responsible for the metabolization of herbicides. This work was carried out to analyse if the metabolization of PROTOX inhibiting-herbicides is the cause of resistance in a multiple resistance biotype of Euphorbia heterophylla. The trial was carry out with a completely randomized experimental design; the treatments were organized in a factorial scheme with 4 repetitions. The factor A was composed by one E. heterophylla biotype susceptible (S) and one multiple resistant to PROTOX and ALS-inhibitors (MR) and the factor B was composed by the application of fomesafen and lactofen herbicides isolated or in tank-mixture with the organophosphate insecticide metamidophos, and an untreated-check. The S biotype presented greater injury and fresh-weight reduction in relation to MR biotype. In MR biotype, there was not difference between the herbicide treatments, regardless of the association with the insecticide in the several evaluations. These results indicate that the combination of organophosphate insecticide metamidophos to PROTOX inhibiting-herbicides does not increase the levels of control of MR biotype compared to isolated application of these herbicides. While not definitive, the results seem to indicate that the metabolism is not the mechanism of resistance of E. heterophylla to the PROTOX inhibiting-herbicides.